Central American economic integration : the politics of unequal benefits - Fagan, Stuart I (Univ. of California. Institute of International Studies BerkeleyUS, 1970)
Presents a detailed and comprehensive description of the process of Central American integration. Applies concepts developed by integration theorists in order to abstract trends from this integration process which are grounded in the facts. Analyzes past trends in order to make some projections about prospects for integration in Central America.